Transscleral photodynamic therapy with a chlorin e6: An experimental study of exposure parameters and therapeutic window - Ernest V. Boiko; Elena V. Samkovich; Irina E. Panova; Alexander A. Ivanov; Sergey B. Shevchenko; Sergey L. Vorobyev; Elizaveta S. Kalashnikova; Victoria G. Gvazava; Elizaveta A. Masian; Alexandra E. Kim (PLoS ONE, 2026)
Purpose To define optimal exposure parameters and the therapeutic window for transscleral photodynamic therapy (TSPDT) with chlorin e6 by evaluating clinical, histological, and thermal effects of subthreshold, therapeutic, and suprathreshold settings in rabbit eyes. Methods The study was conducted on 21 healthy rabbits. TSPDT was performed using a 660 nm laser and chlorin e6 (2.5 mg/kg). Transscleral probes (5 mm: 0.1 W, 0.17 W, 0.3 W; 10 mm: 0.3 W, 0.6 W) with integrated thermosensors were used. Enucleation and histological analysis were performed 14 days post-irradiation. Results Fundus examination on day 14 revealed distinct treatment zones correlating with laser settings. The therapeutic window was defined as 0.14–0.17 W (5 mm probe; power density: 0.693–0.866 W/cm²; energy density: 415.8–519.6 J/cm²) and 0.48–0.6 W (10 mm probe; 0.611–0.764 W/cm²; 366.6–458.4 J/cm²) with 600 s exposure time, achieving selective choroidal damage without scleral or retinal injury (ΔT ≤ 4.5°C). Suprathreshold settings (≥0.3 W for 5 mm; ≥ 0.6 W for 10 mm) induced retinal necrosis (up to 50%) and scleral coagulation (ΔT ≥ 8°C) with power densities exceeding 0.866 W/cm² (5 mm) and 0.764 W/cm² (10 mm). Conclusion TSPDT with chlorin e6 enables selective targeting of intraocular pathological tissues while preserving scleral and retinal integrity. Defining the therapeutic window and using real-time thermal monitoring enhances treatment safety. These findings lay a foundation for clinical protocols for uveal melanoma and other intraocular tumors.